ISLAM-BASED SEXUALITY EDUCATION ON INSTAGRAM (Quantitative Content Analysis of the Instagram Account @taulebih.id) - Karina Danti Aulia Rahma; Yuli Candrasari (International Journal of Education, Vocational and Social Science, 2025)
The use of social media as a platform for disseminating educational content is steadily increasing, including in the realm of Islamic-based sexual education. One such active account is @taulebih.id on Instagram, which consistently shares content on sexual education from an Islamic perspective. This study aims to explore the themes of Islamic-based sexual education presented by the account over six months, from September 2024 to February 2025, analyzing a total of 137 posts. Employing a quantitative content analysis method, this research uses a coding sheet to examine the characteristics of messages based on categorized sexual education themes. The results show that among the six predefined thematic categories, the Physical Biological category emerged as the most frequently featured, representing 26% of the analyzed content, indicating the account’s emphasis on foundational knowledge of the human body. Meanwhile, content under the Islamic Principles and Values category consistently achieved high and stable engagement, suggesting tha audiences strongly receptive to messages framed within Islamic values.